ANALYSIS OF SUITABILITY OF LAND FOR CULTIVATION OF CRACKED FISH (Channa striata) IN PAYA NIE VILLAGE, BIREUEN - Gunawan, S.Pi., M.M (CV Naskah Aceh, 2024)
Snakehead fish (Channa striata) is a type of freshwater fish that is highly economical. Local snakehead fish in the village of Paya Nie Bireuen, Aceh Province are the fish most sought after by local communities, where the livelihood of some of these people is as traditional fish catchers. The problem faced by the community in Paya Nie Bireuen village is the decreasing catch of local snakehead fish, so there is a need for an alternative solution, namely cultivating local snakehead fish. This research aims to discuss the cultivation of snakehead fish (Channa striata) in Paya Nie Village, Bireuen. This sample research began with air collection carried out at 4 (four) points at 4 (four) stations and plankton carried out at 12 (twelve) points at 4 (four) stations. Physical and chemical parameters that are measured directly are: temperature, brightness, depth, dissolved oxygen (DO), salinity, pH, alkalinity, nitrate, nitrite, phosphate. The biological parameters explained in the laboratory are plankton identification which includes diversity, uniformity and dominance. The results of data analysis on water quality using the suspension method show that the land in Paya Nie Bireuen village is included in the appropriate category. Stations I and II showed that the suitability level was not suitable, this result showed that from the 10 parameters measured, only 3 parameters were suitable, namely pH, nitrite content and salinity. In general, it can be concluded that the land in Paya Nie Village is still suitable for cultivating snakehead fish.